A Reaction-Diffusion-Reaction System for Forming Periodic Precipitation Bands of Cu-Fe-Based Prussian Blue Analogues: A Recent Study - Hayashi, Hisashi; Suzuki , Tomoko (New Innovations in Chemistry and Biochemistry Vol. 5, 2021)
We propose a simple and novel system to form precipitation patterns of Cu-Fe-based Prussian blue analogues (Cu-Fe PBA) in agarose gel through coupled electrochemical reactions, reactant ion diffusion influenced by electric field, and precipitation reactions. Several images were acquired with a gradual increase in magnification to observe the crystallites formed in the gel sample. The spatiotemporal evolution, spatial distribution, and crystallite morphologies of the precipitates were investigated by visual inspection, Fe K\(α\) intensity distribution measurements, and optical and scanning electron microscope observations. The observed precipitation patterns and their evolution depended on the applied voltage. Multicolored periodic precipitation bands were stochastically formed under cyclic alternating voltage (4 V for 1 h and then 1 V for 4 h per cycle). The distances between adjacent bands were randomly distributed (0.30 ± 0.25 mm). The sizes and shapes of the crystallites generated in the gel were position-dependent. Cubic but fairly irregular crystallites (0.1–0.8 \(μ\)m) were formed in the periodic bands, whereas definitely cube-shaped crystallites (1–3 \(μ\)m) appeared close to the anode. These cube-like reddish-brown crystallites were assigned to Cu-FeII PBA. In some periodic bands, plate-like blue crystallites (assigned to Cu(OH)2) were also present. Future issues for potential applications of the observed periodic banding for selective preparation of Cu-Fe PBA crystallites were discussed.